Agency and alliance as change factors in psychotherapy - Huber, Julia; Jennissen, Simone; Nikendei, Christoph; Schauenburg, Henning; Dinger, Ulrike (Journal of consulting and clinical psychology, 2021)
Objective: This study examined the reciprocal effects between therapeutic agency, working alliance, and symptoms during psychotherapy. We aimed to predict symptom improvement by previous changes in either agency or alliance. In addition, we examined whether alliance development was predicted by previous changes in agency. Method: A sample of 386 patients in psychodynamic outpatient psychotherapy answered the Therapeutic Agency Inventory (TAI), the Working Alliance Inventory-SR (WAI-SR), and the Symptom Checklist-K11 (SCL-K11) after Sessions 1, 5, 10, 15, and 20. Dynamic panel models were estimated using structural equation modeling. Associations were tested while controlling for autoregressive effects and differentiating within-person changes over time from between-person differences. Results: Increases in agency predicted subsequent symptom improvement. Similarly, increases in alliance predicted subsequent symptom improvement. For agency and alliance, we found a more complex pattern with varying reciprocal effects over time. Conclusions: Findings show evidence for agency and alliance as curative change factors in psychodynamic psychotherapy. The study supports the importance of both agency and alliance and further suggests that both mechanisms may need to be balanced in successful psychotherapies.